2003
DOI: 10.1093/jn/133.1.154
|View full text |Cite
|
Sign up to set email alerts
|

Iron Bioavailability and Utilization in Rats Are Lower from Lime-Treated Corn Flour than from Wheat Flour When They Are Fortified with Different Sources of Iron

Abstract: Although iron bioavailability from wheat flour fortified with iron has been widely studied, the bioavailability of lime-treated corn flour has not been evaluated sufficiently. We compared iron bioavailability and utilization of lime-treated corn flour and wheat flour supplemented with various iron sources. Bioavailability and utilization were determined in Sprague-Dawley rats using the iron balance and hemoglobin depletion-repletion methods. Rats were iron depleted by feeding them a low iron, casein diet for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
5
15
2
Order By: Relevance
“…This finding was in agreement with [30] who reported that there no differences in food intake and body weight gain among groups fed flours supplemented with reduced and increased iron. From the above results, it could be concluded that supplementation the diets with calcium carbonate (as a source of Ca) and calcium phosphate (as a source of Ca + P) reduced the iron absorption in rats fed these diets, which must be continuous to have a long -term influence on serum ferritin, total iron binding capacity, transferrin saturation, hemoglobin, haematocrit, red blood cell and mean corpuscular volume.…”
Section: Resultssupporting
confidence: 93%
“…This finding was in agreement with [30] who reported that there no differences in food intake and body weight gain among groups fed flours supplemented with reduced and increased iron. From the above results, it could be concluded that supplementation the diets with calcium carbonate (as a source of Ca) and calcium phosphate (as a source of Ca + P) reduced the iron absorption in rats fed these diets, which must be continuous to have a long -term influence on serum ferritin, total iron binding capacity, transferrin saturation, hemoglobin, haematocrit, red blood cell and mean corpuscular volume.…”
Section: Resultssupporting
confidence: 93%
“…Strube et al (2002) reported lower weight gain (p <0.01) in Sprague-Dawley rats fed an irondeficient diet. Similar behavior was found by Hernández et al (2003) in Sprague-Dawley rats fed a wheat flour diet with low iron levels.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, Hernández et al (2003) reported that Sprague-Dawley rats fed a alkali-cooked corn flour diet showed lower iron absorption and hemoglobin level than those treated with wheat flour. These authors add that this fact must have occurred because the corn flour contained almost four times more DF and phytate, and the alkaline environment may have contributed to reduce Fe absorption since in this environment, the ferric form predominates and is less absorbed than the ferrous form.…”
Section: Discussionmentioning
confidence: 99%
“…Although carvacrol clearly restricted iron uptake of both ferrous sulfate and ferric citrate, it did not block iron uptake completely like tannic acid, a well-known iron binder, did (17). In general, the bioavailability of ferrous iron is better than that of ferric iron (18)(19)(20), but with ferric citrate larger amounts of ferritin were measured than with ferrous sulfate, indicating that in this system the bioavailability of ferric citrate is better. The higher solubility and stability of ferric citrate than those of ferrous sulfate are probably the reasons for this observation.…”
Section: Discussionmentioning
confidence: 86%